2015
DOI: 10.1017/orp.2015.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship Between Social Support and Durable Return to Work

Abstract: . Investigating the relationship between social support and durable return to work. Retrieved from http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…As the measurement of RTW varies substantially between studies, all RTW status (e.g., partial, full, or sustained RTW [SRTW]) and RTW timing (e.g., duration of absence/compensation) outcomes were included. Table 1 provides details of how RTW was assessed in each study, including the length of follow-up from time of injury where available [2850].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the measurement of RTW varies substantially between studies, all RTW status (e.g., partial, full, or sustained RTW [SRTW]) and RTW timing (e.g., duration of absence/compensation) outcomes were included. Table 1 provides details of how RTW was assessed in each study, including the length of follow-up from time of injury where available [2850].…”
Section: Methodsmentioning
confidence: 99%
“…Supervisor social support was also examined in four studies [40, 42, 47, 50]. Two studies provided mixed support for RTW status; a high quality study [47] indicated supervisor support was a significant univariate predictor of RTW status, although mixed findings emerged in multivariate analyses, while a medium quality study [40] reported no significant finding of supervisor support.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Lysaght and Larmour-Trode (2008) concluded that emotional support was one of the most important features that helped in returning to work. Watt et al (2015) investigated the relationship between social support and a sustainable return to work process among employees returning after occupational injury. Their sample included 110 participants who were asked about their return to work status, relationships with their managers and co-workers and social support outside the workplace.…”
Section: Return To Work and Social Supportmentioning
confidence: 99%